Health-related quality of life in children and adolescents with cochlear implants: self and proxy reports. (September 2014) - Duarte, Ivone; Santos, Cristina Costa; Rego, Guilhermina; Nunes, Rui
Abstract Conclusions: Cochlear implantation appears to favour the perception of improved quality of life (QoL) among children and adolescents. Similar trends were observed among the responses of deaf children and their parents. However, parents of deaf children perceive fewer feelings of provocation than children and adolescents. Objective: This study aimed to assess health-related QoL (HRQoL) among prelingual profoundly deaf children and adolescents with cochlear implants and to compare the responses of these children to those of their parents. Methods: Our sample consisted of deaf children and adolescents with cochlear implants and two control groups: hearing children and adolescents and deaf children and adolescents. The ages of the participants ranged between 8 and 18 years. Parents and children/adolescents were surveyed using the Kidscreen-52, which is a generic instrument for assessing the HRQoL of children and adolescents. Structured interviews were conducted with parents to collect information and clinical histories, and the Graffar scale was used to assess socioeconomic status. Results: The hearing participants exhibited significantly higher QoL than the deaf participants without implants in nearly all domains. In contrast, although hearing participants exhibited a slightly higher QoL than implanted deaf children, these differences were smaller and failed to reach statistical significance.